Unknown costs in a duopoly with differentiated products - Fernanda A. Ferreira (2007)
We consider a duopoly model with unknown costs. The firms' aims are to maximize their profits by choosing the levels of their outputs. The chooses are made simultaneously by both firms. In this paper, we suppose that each firm has two different technologies, and uses one of them following a probability distribution. The utilization of one or the other technology affects the unitary production cost. We show that this game has exactly one Bayesian Nash equilibrium. We analyze the advantages, for firms and for consumers, of using the technology with highest production cost versus the one with cheapest production cost. We also analyze the expected total quantity produced in each situation, which is of particular importance in the case that scanty natural resources are used in the production.